An Analysis of Translation Strategies of Idiom Translation in “Hotel Valhalla: Guide to The Norse Worlds” Companion Book - Kurniawan, Ricky Ilham (Syntax Literate, 2025)
This study examines the translation strategies employed in the Indonesian version of Rick Riordan's "Hotel Valhalla: Guide to the Norse Worlds," focusing on the translation of idiomatic expressions. The companion book, an extension of Riordan's "Magnus Chase and the Gods of Asgard" trilogy, delves into Norse mythology, intertwining ancient mythos with modern narrative techniques. Idioms play a crucial role in the narrative, adding depth and cultural flavor. Following Fernando's classification of idioms into pure, semi, and literal types, and Baker's framework for idiom translation strategies, this research analyzes how idiomatic expressions are translated to maintain fidelity to the original text while ensuring cultural relevance and readability for the Indonesian audience. The study categorizes 249 idioms from the text, including pure, semi, and literal idioms, and identifies five main translation strategies: using idioms of similar meaning but dissimilar form, idioms of similar meaning and form, omission of a play on idiom, omission of entire idioms, and paraphrasing. The findings reveal a predominance of the omission strategies, indicating a preference for simplifying idiomatic expressions to convey their core meanings effectively. The study contributes to the field of translation studies by offering insights into the complexities of translating idiomatic expressions and the challenges faced in preserving their cultural nuances and figurative language in a globalized context.